A Novel Lipid Prognostic Signature of ADCY2, LIPE, and OLR1 in Head and Neck Squamous Cell Carcinoma - Gao, Xiaolei; Zhao, Na; Dong, Liying; Zheng, Xuan; Zhang, Yixin; Ding, Chong; Zhao, Shuyan; Ma, Zeyun; Wang, Yixiang (Frontiers in Oncology, 2021)
Simple Summary Clinically, aberrant lipid metabolism is responsible for overweight and/or obesity. Overweight is considered as an independent factor of cancer risk in 2019. Therefore, lipid metabolic reprogramming is an emerging hallmark of malignancy. It is an urgent need to comprehensively understand the relationship among lipid metabolism and HNSCC and identify a valuable biomarker for predicting prognosis of HNSCC patients. Three new findings were found in this study. Firstly, we identified the lipid-related differentially expressed genes (DEGs) by using the GEO microarrays and TCGA dataset. A novel lipid-related mRNA prognostic signature (LRPS, consisting of ADCY2, LIPE and OLR1) was developed, which could predict the survival and prognosis of HNSCC patients as an independent effective prognostic factor. Secondly, we found that the LRPS could indicate the type of infiltrated immune cells in HNSCC tumor microenvironment. Thirdly, we verified that the LPPS score could interpret the TP53 status of HNSCC. Our new findings indicated that LRPS has a potential to be a promising indicator of overall survival, TP53 status, and immune characteristics in HNSCC, and perhaps can monitor and guide the treatment efficacy and prognosis of HNSCC in the future. Background Head and neck squamous cell carcinoma (HNSCC) is characterized by a high frequency of lymph node metastasis and a high mortality. Lipid metabolic reprogramming is an emerging carcinogen as its role in fulfilling cancer growth and spread. However, little is known about the correlation between lipid metabolism and HNSCC. Materials and Methods Expressions of lipid-related genes were obtained from the Cancer Genome Atlas (TCGA) and Gene expression Omnibus (GEO) databases for differential and functional analyses. A total number of 498 patients from TCGA with complete information were included to identify a lipid-related prognostic signature (LRPS), based on ADCY2, LIPE, and OLR1, by using univariate and multivariate Cox regression analyses. LRPS-high and LRPS-low groups were accordingly divided to pathway and cell enrichment analyses. Results LRS-low patients had a better overall survival and relapse - free survival than LRS-high ones in HNSCC. The LRPS-high group was significantly related to perineural invasion of cancer, cancer-related pathways, high TP53 mutation rate, high proportion of natural killer T cells (NKT), dendritic cells, monocytes, Treg, and M1 and M2 macrophage infiltration in HNSCC tumor tissues. Conversely, the LRPS-low group correlated with DNA damage-related and T-cell-regulated pathways, low frequency of mutated TP53, and high infiltration of B cells and CD4+ effector cells including Th1 and Th2. Conclusion LRPS has a potential to be a promising indicator of overall survival, prognosis, TP53 status, and immune characteristics in HNSCC.